HIGHER EDUCATION IN THE DIGITAL MARKETING AGE: EVALUATING THE COST-EFFECTIVENESS OF INSTAGRAM CAMPAIGN AD FORMATS USING A/B TESTING - Mihajlović, Aleksandar; Gajić, Jelena (The European Journal of Applied Economics, 2025)
In the digital marketing age, higher education institutions are increasingly utilizing social media platforms such as Instagram to enhance their visibility and attract prospective students. This study examines the cost-effectiveness of higher education institutions' Instagram marketing campaigns through A/B testing, focusing on different advertising formats with the same creative approaches. By comparing static images with animated images (in the form of video), the research aims to identify the format that delivers superior cost efficiency for predefined target groups. The analysis indicates that campaigns using static image format are more cost-effective, demonstrating lower Costs per Click (CPC), Cost per Landing Page View (CPLPV), and Cost per Registration (CPR). Moreover, the study emphasizes that Carousel posts outperform video ads significantly in terms of return on investment (ROI), with Carousel campaigns achieving approximately 32.45% higher returns. The findings underscore the importance of audience segmentation, noting that different age groups and genders respond variably to marketing efforts. Despite some limitations, such as sample size and timeframe, the results validate the study's conclusions and underscore the effectiveness of Carousel posts in strengthening institutional image and engagement. This study offers important insights and perspectives for refining and optimizing Instagram marketing strategies in higher education, that can contribute to increasing enrollment and institutional visibility.
Keywords: A/B testing, Advertising formats, Social media, Creative approach, ROI